AUGMENTED REALITY TECHNOLOGY-BASED PAI LEARNING MODEL: POTENTIAL AND CHALLENGES IN MODERN ISLAMIC EDUCATION - Wanda Faris Wahyudi; Muhammad Munif (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The rapid development of digital technology is driving the world of education to continuously adapt, including in the teaching of Islamic Religious Education (PAI). Technology-based innovations such as Augmented Reality (AR) provide new opportunities to deliver more interactive, contextual, and engaging learning for students. Through AR integration, abstract religious concepts can be visualized in three dimensions, making them easier to understand and internalize. This study aims to analyze the potential, capabilities, and challenges of implementing AR in PAI learning as part of efforts to modernize Islamic education in the digital era. The method used is a literature study with a descriptive qualitative approach through a review of various journals, scientific articles, and relevant previous research results. The results show that the application of AR can increase student interest in learning, strengthen understanding of spiritual values, and create meaningful and enjoyable learning experiences. However, the implementation of this technology still faces several obstacles such as limited digital infrastructure, a lack of technological literacy among PAI teachers, and the unequal readiness of Islamic educational institutions to integrate technology into the curriculum. Therefore, teacher training, policy support, and the development of AR content that aligns with Islamic values are needed for optimal and ethical implementation.